PERAN PENYULUH AGAMA ISLAM DALAM PENCATATAN PERNIKAHAN PADA KANTOR URUSAN AGAMA (KUA) TEMBILAHAN HULU - Radiah Radiah; Ahmad Rifa'i; Muhammad Fauzan (Indragiri Research Center (ingreat), 2026)
This study aims to examine the role of Islamic Religious Counselors in marriage registration at the Office of Religious Affairs (KUA) of Tembilahan Hulu and to identify the efforts, obstacles, and supporting factors in increasing public awareness. This research uses a qualitative method with a descriptive approach through interviews, observations, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, with validity tested using triangulation. The results show that Islamic Religious Counselors have performed their roles optimally through educational, informative, and facilitative functions. The efforts include counseling activities, the use of information media, interpersonal communication approaches, and collaboration with community leaders. The obstacles include low public understanding, the practice of unregistered marriages, geographical limitations, and limited counselor resources. Supporting factors include institutional support from KUA, cooperation with community leaders, and active community participation. Thus, the role of Islamic Religious Counselors is considered effective in increasing public awareness of marriage registration.